A Conceptual Model of Referee Efficacy - Guillén, Félix; Feltz, Deborah L. (Frontiers in Psychology, 2011)
This paper presents a conceptual model of referee efficacy, defines the concept, proposes sources of referee specific efficacy information, and suggests consequences of having high or low referee efficacy. Referee efficacy is defined as the extent to which referees believe they have the capacity to perform successfully in their job. Referee efficacy beliefs are hypothesized to be influenced by mastery experiences, referee knowledge/education, support from significant others, physical/mental preparedness, environmental comfort, and perceived anxiety. In turn, referee efficacy beliefs are hypothesized to influence referee performance, referee stress, athlete rule violations, athlete satisfaction, and co-referee satisfaction.